Determinants of recent inflation in Pakistan: Revisit - Qazi Masood Ahmed; Sulaiman D. Muhammad; Muhammad Noman; Ghulam Rasool Lakhan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
This paper explores the short and long run dynamics of inflation in Pakistan using Johansen Co-integration Technique covering data from 1972-73 to 2012-13. Consumer Price Index (CPI), Exchange Rate (ER), Government Borrowing (GB), Non-Government Borrowing (NGB), Real GNP (RGNP), Indirect Taxes (IT), Growth Rate of Money Supply (GMS), Import Price Index (IPI), Real Demand relative to Real Supply (RD/RS) and Wheat Support Price (WSP) Money Supply (MS) are taken as indicators. The result shows a long run relationship among the selected variables. It is found that the ER is the most significant factor of inflation in 2011-12, GB, IT, GMS, IPI, RD/RS. It represents the output gap consist of fiscal policy inflation is highly significant.
Keywords: 330; consumer price index; inflation; exchange rate; government borrowing; real GNP; indirect taxes; growth rate of money supply; import price index; wheat support price